Eis em cena o grotesco: ecos na poética de Álvares de Azevedo e de Bernardo Guimarães - Costa, Ana Carolina Pereira da (2023)
The brazilian romantic lyric, especially the ultra-romantic one, expresses the most perfect song that the egotistic facet comprehends. However, there is another facet of the poetry from the second romantic generation that delved into other aesthetics, among them the grotesque. The ironic and satirical poetry of the period did not resonate with the canon, as humor went against the nationalist intentions undertaken. Therefore, the presence of laughter in brazilian romanticism occupied marginal spaces, used as an alternative to the exhaustion of sentimentality, a plural context for theorizations about modern poetry. Thus, the present research proposes to analyze the ironic and satirical poetry of Álvares de Azevedo and Bernardo Guimarães in light of relevant contradictions, seeking guidance in studies on the grotesque. The theoretical concepts of the grotesque explored are present in the theories of Bakhtin (2010), Hugo (2007), and Kayser (2013), aligned with theoretical contributions on laughter in Minois (2003) and modern poetry in Schlegel (1992, 2016). The analysis of the works of the mentioned poets started from recurring figures in the poems, such as the woman, death, and the poet, in order to identify how the grotesque manifests itself in this discordant lyric.